Socialization of the Use of Kersen Leaf Boiled Water (Muntingia calabura) as a Nonpharmacological Therapy for Hypertension in the Elderly in Mojosarirejo Village, Driyorejo District, Gresik Regency in 2023 - Billah, Illa; Wardah, Beta; Audina, Miea; Rismei, Ajeng; Dewi, Uke Maharani; Dwijayanti, Ira (UNUSA Press, 2023)
Hypertension is an increase in blood pressure in the arteries. Hypertension is an asymptomatic condition, in which abnormally high pressure in the arteries leads to an increased risk of stroke, aneurysm, heart failure, heart attack and kidney damage. One of the non-pharmacological therapies to reduce hypertension is a decoction of kersen leaves. To identify the level of knowledge that kersen leaf boiled water can help reduce hypertension in Mojosarirejo Village, Driyorejo District, Gresik Regency in 2023. The method used is the lecture method with the media of posters and leaflets. From the results of the study, there were 34 respondents who had knowledge about the benefits of kersen leaf decoction for hypertension patients, namely 5 people (15%), while those who did not have Knowledge about the benefits of kersen leaf decoction for hypertension patients is as many as 29 people (85%).